Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3168/jds.2009-2678
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of cell junctions induces apoptosis and reduces synthetic activity in lactating goat mammary gland

Abstract: Although it is known that disruption of the cell junctions in the mammary gland induces a decrease in milk yield, the cellular mechanisms involved in milk secretion reduction during mammary cell junction disruption are not well understood. The aim of this study was to investigate the cellular regulations taking place after cell junction disruption in the mammary gland of goats. We performed intramammary infusions of Ca chelators to induce cell junction disruption. In a first group of 5 goats, intramammary infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
(47 reference statements)
2
17
0
Order By: Relevance
“…hypothesized that the switch of tight junctions to a leaky state during the first 24 h of ODM may be part of the acute regulatory mechanism decreasing milk yield. This assumption is consistent with data from oligonucleotide-array study (Littlejohn et al, 2010) or from studies using calcium chelators to mimic the effect on mammary epithelium integrity (Stelwagen et al, 1995;Ben Chedly et al, 2010). These studies reported decreased synthetic activity and the induction of cell death.…”
Section: Plasma Lactose Concentrations Are Poorly Correlated With Milsupporting
confidence: 87%
“…hypothesized that the switch of tight junctions to a leaky state during the first 24 h of ODM may be part of the acute regulatory mechanism decreasing milk yield. This assumption is consistent with data from oligonucleotide-array study (Littlejohn et al, 2010) or from studies using calcium chelators to mimic the effect on mammary epithelium integrity (Stelwagen et al, 1995;Ben Chedly et al, 2010). These studies reported decreased synthetic activity and the induction of cell death.…”
Section: Plasma Lactose Concentrations Are Poorly Correlated With Milsupporting
confidence: 87%
“…However, our finding revealed that the disruption of tight junctions occurs only on the first day of ODM application and disappears thereafter. The disruption of mammary epithelium has been associated with a decrease in the expression of constitutive tight and adherens junctions protein such as occludin and E-cadherin respectively (Ben Chedly et al, 2010). The similar labelling intensity of E-cadherin observed for the ODM/TDM and control groups after 2 days of the ODM period suggests that adherens junctions was not affected by ODM after 2 days of treatment.…”
Section: Discussionmentioning
confidence: 90%
“…ECM) was sufficient to induce expression of casein genes without the addition of any growth factor, highlighting the essential role of integrins [123,134]. Interestingly, in goat mammary tissue in vivo and in vitro disruption of cell junctions strongly reduced milk yield and expression of casein and alpha-lactalbumin [135].…”
Section: Regulation Of Milk Protein Expressionmentioning
confidence: 99%